2018
DOI: 10.1590/1678-4324-2017160756
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Quorum Sensing Potential of Antioxidant Quercetin and Resveratrol

Abstract: Quorum sensing system plays an active role in the regulation of pathogenicity of many microorganisms. Inhibition of pathogenicity or virulence factors will increase the success of treatment by preventing the development of antibiotic resistance. In this study, anti-quorum sensing activities of quercetin and resveratrol compounds, which have antioxidant property without damaging to host, have been determined via using biosensor bacteria: Chromobacterium violaceum ATCC 12472 and Chromobacterium violaceum CV026. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Similar results were reported by He et al [19] that demonstrated the feasibility of attenuating the tolerance of P. aeruginosa to azithromycin by using marine oligosaccharides. Increased H 2 O 2 susceptibility was unexpected at rst, as quercetin is known as important antioxidants [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by He et al [19] that demonstrated the feasibility of attenuating the tolerance of P. aeruginosa to azithromycin by using marine oligosaccharides. Increased H 2 O 2 susceptibility was unexpected at rst, as quercetin is known as important antioxidants [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…It is found commonly in many fruits, vegetables, leaves and grains [6]. Several investigations have reported the anti-microbial, anti-quorum sensing, anti-oxidant, anti-carcinogenic, anti-in ammatory, anti-apoptotic and anti-histamine effects of quercetin [4,6,11,12]. One strategy that can be useful in the treatment of MDR P. aeruginosa infections is the synergy using combinations of natural compounds with antibiotics leading to enhancement of antibacterial activity of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Using biofilm formation assay, Ouyang and colleagues [136] reported that quercetin decreases adhesion and biofilm formation in Pseudomonas aeruginosa, as well as swarming motility and expression of biofilm-associated genes. Quercetin also showed significant reduction in QS-dependent phenotypes, including violacein Quercetin has been investigated by several researchers for its anti-QS activities [79,83,[131][132][133][134][135][136]. Results revealed that the actions of quercetin against QS are diverse and multiple, and depend on the bacterial strain tested and the experimental method used.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…The stem bark of S. acoca contains quercetin, quercetin-3-O-α-lrhamnoside, kaempferol, betasitosterol [31]. Studies have shown that quercetin and its derivates posses significant anti-QS properties against C. violaceum and P. aeruginosa [32][33]. Possibly, the anti-QS activity of SAE may be attributed to its bioactive flavonoid contents.…”
Section: (Iii and Iv)mentioning
confidence: 99%